Peran Lembaga Keuangan Dalam Mencegah Jeratan Pinjaman Online Ilegal - Rahmat Rudiyanto (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2025)
The rapid growth of information and communication technology has driven transformation in the financial sector, one of which is through the presence of digital-based loan services or online loans (pinjol). Although ease of access and speed of process are the main advantages of this service, in reality, many people are trapped in illegal online loans that operate outside the supervision of official authorities. These illegal loans often ensnare people with very high interest rates, inhumane collection practices, and misuse of personal data, resulting in serious social and psychological impacts. In this context, the role of financial institutions, both conventional banking institutions, cooperatives, and financial technology companies (fintech) registered and supervised by the OJK, is very crucial. This article aims to analyze how financial institutions can contribute to preventing the trap of illegal online loans through a financial literacy approach, expanding access to formal financial services, developing inclusive and affordable financing products, and collaborating with the government and supervisory authorities. In addition, this study also examines the importance of strengthening regulations, law enforcement against illegal lenders, and massive public education campaigns about the risks of illegal pinjol. Based on secondary data analysis and recent literature studies, this article concludes that efforts to overcome the rampant illegal online loans require synergy between financial institutions, supervisory authorities, and the active role of the community. Financial institutions that function optimally are not only service providers, but also agents of change in shaping healthy financial behavior and encouraging national financial inclusion.